Atomistic Simulations of Defect Formation Processes During Crystallization of Melted Silicon - Manabu lshimaru (The Minerals, Metals and Materials Society, 2001)
Solid-liquid interfaces as well as defect formation processes during crystallization of melted silicon (Si) have been examined by using molecular-dynamics (MD) simulations. The ordinary Langevin equation employing the Tersoff interatomic potential was used for the calculation of the atomic trajectories. A solid-melt interface has a tendency to form {]] I} microfacets during the crystal growth in the [001] direction, while it is essentially flat during the (Ill) crystallization. Because of the difference of the interfacial structures, the structures of grown-in defects and defect evolution depend strongly on the growth direction. We discuss defect structures and their formation processes within the context of our results as well as previous experimental observations.